Phytosterol and Flavanone From Roots of Zanthoxylum budrunga - Shetgiri, N.P.; Rege, L.N. (Asian Journal of Chemistry, 2010)
Phytochemical studies on the roots of Zanthoxylum budrunga,collected from Palaye, a village in Northern region of Goa, India,resulted in the isolation of two compounds. Their structures havebeen established as (3β, 4α, 5α, 24Z)-4-methyl stigrnasta 7,24(28)diene-3-ol (I) and 4',5,7-trihydroxy-3'-methoxyflavanone (II) on thebasis of spectroscopic techniques and chemical means. These compoundshave been screened for their antimicrobial activity.